if g(x) is the inverse of f(x) = 4x+12.
Explanation:
Given that,
f(x) = 4x + 12
To find g(x) Let f(x) = y
y = 4x+12
Subtract 12 from both side
y -12 = 4x + 12 - 12
y – 12 = 4x
Solve to find x
![x=(y)/(4)-(12)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v2xnmy4g6nyfflgbc7cwhfcbw2ooeos1g4.png)
![x=(y)/(4)-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fzdi5anwd9mhtwqjylz6lhjnudgz7m7tkz.png)
We know that from f(x) = y
![x=f^(-1)(y)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vouj7613os4tahb6hicqmde89zthv323ws.png)
![f^(-1)(y)=(y)/(4)-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/a0a4infr526qsvx64bwjajm2ojl29y30ve.png)
From the question we know that g(x) is the inverse of f(x)
Thus
when g(x) is the inverse of f(x)=4x+12.